The mark of Athena - Riordan, Rick (Riordan, Rick. Heroes of Olympus, 2019)
Annabeth has been away from Percy for six months, but at last they are about to be reunited. However, Annabeth fears Percy's time at Camp Jupiter may have turned him to the Roman ways instead of the Greek and that he may no longer need her even if she needs him. Annabeth has been tasked by her mother, Athena, with following Athena's mark to get revenge on her mother's enemies--on top of Annabeth and the other demi-gods' task of fulfilling the prophecy and sealing the Doors of Death.